Epidemiological analysis of infant deaths from external causes in Sergipe in the years 2015 to 2020 (Research, Society and Development, 2023)
Objectives: to collect epidemiological data on deaths caused by external causes in children aged 0 to 9 years in the state of Sergipe between the years 2015 and 2020 and critically analyze them. Methodology: Analytical epidemiological study carried out from secondary data accessed by DATASUS, using as a filter the CIDs transport accidents, falls, drowning and accidental submersion, exposure to smoke, fire and flames and poisoning and/or intoxication by or exposure to harmful substances, restricted to the age group from 0 to 9 years old, analyzing the deaths recorded between the years 2015 to 2020. Results: the study showed that there were 85 deaths from external causes in Sergipe in the period between 2015 and 2020, with a decrease during the first four years and a slight increase in 2020 compared to the previous year, which may be related to the pandemic. The highest prevalence of deaths in this period was due to traffic accidents, followed respectively by drowning and submersion, falls, exposure to smoke, fire and flames, poisoning and/or intoxication. Discussion: Despite guaranteeing the right to protection of the child by the Statute of the Child and Adolescent, cases of death due to accidents in childhood are still a serious public health problem in Sergipe, given that it coincides with the Brazilian reality and seems to be a trend common to countries where it has occurred, where it is the leading cause of infant death. Conclusion: Due to its epidemiological and social importance, it is necessary to curb the prevalence of this condition through preventive practices and encourage the dissemination of first aid knowledge so that, when it is not possible to prevent them, act early and avoid unfavorable abandonment.